Chemical assayed manganese nodule samples from the Blake Plateau by Deepsea Ventures Inc. (1969-1971) - Deepsea Ventures Inc. (PANGAEA, 2022)
Deepsea Ventures Inc. conducted a series of assessments and tests regarding the mining of manganese nodules in the Blake Plateau area. These operations were made using the R/V Prospector from 1969 until 1971. Retrieved samples were analysed using Atomic Absorption Spectrometry.